Genome-wide identification and characterization of the bZIP gene family and their function in starch accumulation in Chinese chestnut (Castanea mollissima Blume) - Zhang, Penglong; Liu, Jing; Jia, Nan; Wang, Meng; Lu, Yi; Wang, Dongsheng; Zhang, Jingzheng; Zhang, Haie; Wang, Xuan (Frontiers in Plant Science, 2023)
The transcription factors of basic leucine zipper (bZIP) family genes play significant roles in stress response as well as growth and development in plants. However, little is known about the bZIP gene family in Chinese chestnut (Castanea mollissima Blume). In this study, we identified 59 bZIP genes that were unevenly distributed in the chestnut genome and renamed them CmbZIP01 to CmbZIP59. These 59 CmbZIP genes were clustered into 13 clades that had clade-specific motifs and structures. A synteny analysis revealed that segmental duplication was the major driving force of expansion of the CmbZIP gene family. A total of 41 CmbZIP genes had syntenic relationships with four other species. The results from the expression pattern and co-expression network analyses indicated that CmbZIP04, CmbZIP13, CmbZIP14, CmbZIP33, CmbZIP35, CmbZIP38, and CmbZIP56 may be important in regulating starch accumulation in chestnut seeds. Yeast one-hybrid assays showed that transcription factors CmbZIP13 and CmbZIP35 might participate in starch accumulation in the chestnut seed by binding to the promoters of CmISA2 and CmSBE1_2, respectively. Our study provided basic information on CmbZIP genes, which can be utilized in future functional analysis and breeding studies.